Gravitational collapse and the information loss problem - Kesselly, Alton Vanie (Department of Mathematics and Applied Mathematics, 2016)
This thesis is intended to critically review the standard black holes. In this thesis, we used the intractability of the black hole Information loss problem and the current crisis stirred up by the black hole Firewall paradox to support the argument that nature is better off without black holes.